1979
DOI: 10.1104/pp.63.4.722
|View full text |Cite
|
Sign up to set email alerts
|

Protoplasts Surviving Freezing to −196 C and Osmotic Dehydration in 5 Molar Salt Solutions Prepared from the Bark of Winter Black Locust Trees

Abstract: Free protoplasts were prepared from the living bark tissue of the trunk of summer and winter black locust trees by enzymic digestion of thin slices of the tissue for 3 hours in a medium containing 2% Onozuka cellulase, 2% Rhozyme pectinase, and 2% Driselase in mannitol solutions using 0.4 molar mannitol for summer tissue and 1.0 molar mannitol for winter tissues.Cleaned suspensions of protoplasts and also thin slices of tissue with cells intact were frozen to temperatures of -10 C, -20 C, -30 C, -40 C and liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 9 publications
(15 reference statements)
1
5
0
Order By: Relevance
“…Because the mutant CW15+ lacks the cell wall found in the wild-type, this indicates that disruption of the plasma membrane/cell wall interaction was not a primary cause of freezing injury in C. reinhardii. Similar conclusions have resulted from studies of isolated protoplasts of higher plant cells (19).…”
supporting
confidence: 78%
“…Because the mutant CW15+ lacks the cell wall found in the wild-type, this indicates that disruption of the plasma membrane/cell wall interaction was not a primary cause of freezing injury in C. reinhardii. Similar conclusions have resulted from studies of isolated protoplasts of higher plant cells (19).…”
supporting
confidence: 78%
“…However, it is not yet known whether AFPs also exert cryoprotective effects in planta as observed in experiments using fish AFPs. These experiments are difficult to conduct with intact plants; however, suspension cells and protoplasts isolated from non‐acclimated and cold‐acclimated winter rye, bromegrass and the woody species Robinia pseudoacacia have been shown to exhibit changes in freezing tolerance that are comparable with the corresponding tissues and organs (Siminovitch 1979, Singh 1981, Chen and Gusta 1982, Ishikawa et al 1995). One advantage of working with protoplasts and suspension cells is that externally applied solutions are more uniformly accessible to the cells.…”
Section: Introductionmentioning
confidence: 99%
“…Siminoviteh et al (1978), however, observed a higher degree of freezing tolerance of protoplasts than of their parent tissue in rye seedlings. Siminovitch (1979) also reported a lower resistance to injury of protoplasts (of black locust bark) frozen in sucrose eompared to intact cells in tissue slices. Singh (1981) pointed out that, to prevent lysis, the released protoplasts require the presence of an external osmoticum.…”
Section: Introductionmentioning
confidence: 91%
“…Released protoplasts from higher plants have been used to study the mechanism of freezing toleranee and cold acclimation. The use of protoplasts not only allows microscopic observations of membrane ehanges (Steponkus et al 1982a), but faeilitates in situ labeling of the plasma membrane with probes (Singh 1979) and avoids the "complications associated with the presenee of eell wall" (Siminovitch 1979) in such studies. When released protoplasts were frozen in an appropriate medium, they exhibited freezing sensitivity similar to or parallel with their tissues of origin (Singh 1979, Steponkus et al 1982a.…”
Section: Introductionmentioning
confidence: 99%